2019
DOI: 10.1007/s42729-019-00031-0
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Kinetics of 2,4-D and Diuron Herbicides in a Urea-Fertilized Andisol

Abstract: Sorption kinetics studies of herbicides, using different models, are an important tool for determining the mechanisms and kinetic parameters that explain the bioavailability and environmental behavior of these compounds. However, little is known about the combined effects of fertilizers and herbicides and how it could modify these processes on the soil. The aim of this study was to evaluate the sorption kinetics of diuron and 2,4-D in an Andisol treated with urea using various kinetic models. The experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Despite being relatively low leverage and low identifiable, sorption parameters ( K FP and n FP ) were not considered for reduction due to the importance of sorption of pesticide in soil . Moreover, these two parameters could be directly measured through sorption kinetic experiments (not performed in the current work). Additionally, the analysis suggests that parameter a CO 2 can be eliminated due to its low impact on model outputs.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being relatively low leverage and low identifiable, sorption parameters ( K FP and n FP ) were not considered for reduction due to the importance of sorption of pesticide in soil . Moreover, these two parameters could be directly measured through sorption kinetic experiments (not performed in the current work). Additionally, the analysis suggests that parameter a CO 2 can be eliminated due to its low impact on model outputs.…”
Section: Resultsmentioning
confidence: 99%
“…The fate and transport of the phenoxy herbicides (adsorption/desorption) in the subsurface are affected by a complex, time-dependent interplay between adsorption and mineralization processes, which are influenced by both the water and organic matter content of the soil as well as its pH. Research on the adsorption of phenoxyacetic acids concerned soils with different degrees of mineralization, different contents of organic materials, different geological origins, and different locations [ 50 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ]. The problem of adsorption and transport of herbicides in the soil has been recently very carefully described and discussed in the review by Paszko et al [ 153 ].…”
Section: Adsorption Of Chlorinated Phenoxyacetic Acids On Non-carbona...mentioning
confidence: 99%
“…At low concentrations, it presents the characteristics of the Freundlich isotherm. 59 The Sips isothermal adsorption model showed that the maximum adsorption capacity of diuron was 69.04 mg g À1 . The R 2 values of the three isotherm models are greater than 0.90, which indicates that they are applicable for explaining the adsorption mechanism.…”
Section: Adsorption Isothermsmentioning
confidence: 99%